Mrs. Seniya Sheh V. Mrs. Belaynesh Matebo & Mr. Sherif Ahmed, Federal Supreme Court Cassation Division;Mrs. Minya G/Silassie V. Mr. Meseret Alemayehu, Federal Supreme Court Cassation Division - Yaze, Worku (Bahir Dar University Journal of Law, 2022)
á‹¨á‰°áˆ˜áˆ¨áŒ¡ ááˆá‹¶á‰½ (á‰ á‰¤á‰°áˆ°á‰¥ áˆ…áŒ áˆ‹á‹ á‹«á‰°áŠ®áˆ©)